Expert System For Personal Computer Mendiagnosa kerusakan Method Using Certainty Factor - Yunus Simare-mare; Fristi Riandari (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Along with the development of information technology, computers today have developed rapidly so that they require a higher technology world. Nowadays computers can be made in the category of human needs, Because they can help or human Facilitate work in various fields. The use of computer laboratories at Sei Bamban YAPIM Private Vocational School is very dense, so the level of computer damage is greater, both in terms of hardware and software. Here the author will discuss Expert Systems to Diagnose Damage to Personal Computers, the Certainty Methods Method is one of the Expert System Methods to Be Able to diagnose damage to a Personal Computer. In this case the Certainty Factor method is used to diagnose damage to the Personal Computer through existing symptoms. The damage is taken from symptoms that may occur and then given a decision and provide Appropriate solutions to Overcome damage to the Personal Computer. The symptoms of damage to the Personal Computer will then be changed in the form of applications. To create an application the author uses Microsoft Visual Studio 2010. This thesis will explain the damage report and solutions for Personal Computer.